SOCIAL MEDIA INFLUENCERS AND BRAND LOYALTY: ANALYZING THE DYNAMICS OF TRUST AND CONSUMER DECISION-MAKING - Fikri, Maiza (Penelitian dan Pengembangan Ilmu, 2025)
The role of social media influencers (SMI) has undergone a significant transformation in digital marketing, shifting from mere product endorsers to opinion leaders who shape consumer perception and loyalty. However, there is a void in the literature that systematically integrates the role of trust as a mediator between influencer characteristics and brand loyalty. This research aims to examine how trust in social media influencers mediates the relationship between influencer characteristics—including credibility, attractiveness, and expertise—and brand loyalty. This study uses the Systematic Literature Review (SLR) method with the PRISMA approach to identify and synthesize 41 peer-reviewed articles from Scopus, Web of Science, and Springer databases published between 2015–2024. Data analysis was carried out through thematic analysis based on the Source Credibility Theory and Trust Mediation Model. Findings suggest that trust serves as a key mediator linking influencer characteristics with brand loyalty. Trust is formed through aspects of trustworthiness, authenticity, and parasocial relationships which strengthen consumers' emotional ties and commitment to the brand. Parasocial interactions in particular increase repurchase intentions and brand advocacy. The study also confirms the importance of an influencer's credibility, social appeal, and expertise in building audience trust. Trust is a strategic element that must be managed explicitly in influencer-based marketing campaigns to increase brand loyalty. This research enriches the digital marketing literature by integrating consumer psychology theory and providing practical guidance for brand managers in selecting and managing authentic and credible influencers.